Reproductive studies of Anchoa marinii Hildebrand, 1943 (Actinopterygii: Engraulidae) in the nearby-coastal area of Mar Chiquita coastal lagoon, Buenos Aires, Argentina - López,Sofía (2015)
The aim of the present study provides the first results on the reproductive biology of the anchovy, Anchoa marinii, in a nearby-coastal area of Mar Chiquita coastal lagoon, 37º32'00"S 57º19'00"W, Argentina. To perform this, we employed mainly female gonads, at both microscopic and macroscopic levels. The oocyte diameter distribution and the microscopy analysis of oocytes, showed different batches of growing oocytes, suggesting that the anchovy is a multiple spawner, with constant oocytes recruitment all over the reproductive season. The batch fecundity ranged between 749 and 3,207 oocytes for females, and the relative fecundity ranged from 127 to 422 yolked oocytes per female gram (ovary free). The fecundity estimation has been made with yolked oocytes. No correlation between the fecundity estimation and female size and total weight (without ovary) has been found. The estimated L50 values were 74.13 and 73.76 mm TL for females and males, respectively. Shoals of females in advanced maturity phase were recorded, between December to April in the study area. During this period a significant increase of species abundance was correlated with water temperature increase (above 16°C). This fact, together with the detection of post-ovulatory follicles, indicated the existence of reproductive events in the nearby-coastal area of Mar Chiquita coastal lagoon.